A formação do fisioterapeuta em residência multiprofissional no município de Campinas - Carlini, Alexandra Cristina Cruz [UNIFESP] (2019)
The purpose of this research was to investigate the formation of physiotherapists in the Multiprofessional Health Residency of the Ouro Verde Hospital Complex and Dr. Mário Gatti Hospital in the city of Campinas. A descriptive and exploratory study was developed through qualitative methodology. The context of this research was composed of two Multiprofessional Residency Programs, which contained physiotherapy graduates in 2018. The population of this research consisted of two Multiprofessional Health Residency Program Coordinators, four Physical Therapist Preceptors and 15 physical therapist residents. All participants signed the Informed Consent Form. The data were collected through a semi-structured interviews with the Coordinators and Preceptors and the focus group with the resident physical therapists. Data were evaluated through thematic content analysis. In the end, we concluded that both programs develop training at the three levels of care, from a multiprofessional perspective, to build an Interprofessional Health Education. The challenges were the budgetary difficulties, inadequacy of the number of professionals in the institutions and preceptors, as well as the presence of systematic pedagogical qualification for the actors involved. It is also noteworthy that there is no recognition of programs by the National Commission for Multiprofessional Residency in Health. Both programs are important tools for the use and qualification of residents physiotherapists.